Analisis Kemampuan Pemecahan Masalah Mahasiswa Semester 2 Pada Materi Geometri Bidang Segitiga Berkonteks Kearifan Lokal Menggunakan Metode Newman - Aghniya Rahmi; Nurul Sakinah; Steven Samuel Harianja; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the problem-solving abilities of second-semester students of Mathematics Education at Universitas Negeri Medan on triangle plane geometry material contextualized with the local wisdom of North Sumatra, using Newman's Error Analysis (NEA) framework. A descriptive quantitative method supported by qualitative analysis was employed. The research subjects consisted of 30 students selected through purposive sampling. The data collection instrument comprised five essay questions based on ethnomathematics, incorporating contexts such as Gorga Batak ornaments, Rumah Bolon architecture, Honai, and ulos motifs. Data analysis was conducted by categorizing student errors into five Newman stages: Reading, Comprehension, Transformation, Process Skills, and Encoding, with descriptive percentage calculations. The results indicate that the highest error rate occurred at the Transformation stage (42.3%), followed by Process Skills (35.7%), Comprehension (10.8%), Encoding (6.0%), and Reading (5.2%). These findings suggest that students face significant barriers in horizontal mathematization—namely, the ability to convert contextual situations into formal mathematical models. Local wisdom contexts were found to enhance student engagement in the early stages of problem-solving but were insufficient to promote formal deductive reasoning. This study recommends the development of more structured ethnomathematics-based teaching materials oriented toward formal mathematical thinking processes.